Hubungan Efek Samping Suplemen Zat Besi (Fe) dengan Kepatuhan Ibu Hamil TM III di Wilayah Kerja Puskesmas Cukir Kecamatan Diwek Kabupaten Jombang - Indah Tri Hardiyanti; Ita Eko Suparni (JURNAL ILKES : Jurnal Ilmu Kesehatan, 2018)
Anemia in pregnancy is one of the risks to watch out for because it can affect the health of the mother and fetus. One factor of anemia in pregnant women is maternal disobedience in consuming iron (Fe) supplements. The purpose of this research was to determine the correlation of side effects of iron (Fe) supplement with the compliance of pregnant mother TM III in Work Area Cukir Public Health Center, Diwek District, Jombang Regency. The design of this research used an analytic survey with a retrospective cohort approach in Work Area Cukir public Health Center in Diwek District, Jombang Regency on June 27 2018 to August 27 2018. The independent variable in this research was Side Effects and dependent variable compliance.Population in this research is pregnant mother TM III and was used simple random sampling technique from the population of 94, there were 76 Instrument respondents who used recall data and interview guide. This research uses Chi-Square statistical test with a significance level of 0.05. The results showed that most of the 58 (76.3%) pregnant mother experienced side effects of nausea and vomiting and constipation and found that most 51 (67.1%) were not compliant in consumption iron (Fe) supplements. Analysis of the results of this research with the Chi-Square test showed there was a correlation between the side effects of iron (Fe) supplementation and the compliance of pregnant mother TM III in Work Area Cukir Public Health Center, Diwek District, Jombang Regency, the value (p value = 0,000<ɑ = 0,05). value (r) 0,513 moderate relationship level. The dose of iron (Fe) supplements above 60 mg can cause side effects that are not acceptable in pregnant mother resulting in non-compliance in drug use. Pregnant mother need to consumption Fe tablets during pregnancy, because maternal iron needs increase during pregnancy.